The Social Context of “Do-It-Yourself” Brain Stimulation: Neurohackers, Biohackers, and Lifehackers - Wexler, Anna (Frontiers in Human Neuroscience, 2017)
The “do-it-yourself” (DIY) brain stimulation movement began in earnest in late 2011, when lay individuals began building stimulation devices and applying low levels of electricity to their heads for self-improvement purposes. To date, scholarship on the home use of brain stimulation has focused on characterizing the practices of users via quantitative and qualitative studies, and on analyzing related ethical and regulatory issues. In this perspective piece, however, I take the opposite approach: rather than viewing the home use of brain stimulation on its own, I argue that it must be understood within the context of other DIY and citizen science movements. Seen in this light, the home use of brain stimulation is only a small part of the “neurohacking” movement, which is comprised of individuals attempting to optimize their brains to achieve enhanced performance. Neurohacking itself is an offshoot of the “life hacking” (or “quantified self”) movement, in which individuals self-track minute aspects of their daily lives in order to enhance productivity or performance. Additionally, the home or DIY use of brain stimulation is in many ways parallel to the DIY Biology (or “biohacking”) movement, which seeks to democratize tools of scientific experimentation. Here, I describe the place of the home use of brain stimulation with regard to neurohackers, lifehackers, and biohackers, and suggest that a policy approach for the home use of brain stimulation should have an appreciation both of individual motivations as well as the broader social context of the movement itself.